Clocks Ticking in the Dark: A Review of Biological Rhythms in Subterranean African Mole-Rats - Oosthuizen, Maria K.; Bennett, Nigel C. (Frontiers in Ecology and Evolution, 2022)
Biological rhythms are rhythmic fluctuations of biological functions that occur in almost all organisms and on several time scales. These rhythms are generated endogenously and entail the coordination of physiological and behavioural processes to predictable, external environmental rhythms. The light-dark cycle is usually the most prominent environmental cue to which animals synchronise their rhythms. Biological rhythms are believed to provide an adaptive advantage to organisms. In the present review, we will examine the occurrence of circadian and seasonal rhythms in African mole-rats (family Bathyergidae). African mole-rats are strictly subterranean, they very rarely emerge aboveground and therefore, do not have regular access to environmental light. A key adaptation to their specialised habitat is a reduction in the visual system. Mole-rats exhibit both daily and seasonal rhythmicity in a range of behaviours and physiological variables, albeit to different degrees and with large variability. We review previous research on the entire circadian system of African mole-rats and discuss output rhythms in detail. Laboratory experiments imply that light remains the strongest zeitgeber for entrainment but in the absence of light, animals can entrain to ambient temperature rhythms. Field studies report that rhythmic daily and seasonal behaviour is displayed in their natural habitat. We suggest that ambient temperature and rainfall play an important role in the timing of rhythmic behaviour in mole-rats, and that they likely respond directly to these zeitgebers in the field rather than exhibit robust endogenous rhythms. In the light of climate change, these subterranean animals are buffered from the direct and immediate effects of changes in temperature and rainfall, partly because they do not have robust circadian rhythms, however on a longer term they are vulnerable to changes in their food sources and dispersal abilities.